Canadian Islamic Schools: Unravelling the Politics of Faith, Gender, Knowledge, and Identity by Jasmin Zine (Toronto: University of Toronto Press, 2008. 369 pages.) (American Journal of Islam and Society, 2009)
Over the last two to three decades, a number of factors have ensured thatwestern Muslims and Islam have become socially and politically far moreembedded and visible in western liberal democracies. For example, a largesegment of new (post-1965) immigrant religious minority communities settlingin western liberal democracies, including Canada, are of the Muslimfaith. Moreover, an increasing number of educated, professional westernbornMuslims consider, unlike their immigrant parents, their countries ofbirth as their “home.” Furthermore, the politicization of Islam and the natureof the current state of international affairs, in which issues pertaining toMuslims and Islam often take central place, have highlighted the publicprominence of Islam and its adherents in theWest.This situation has problematized and generated a number of debatesrelating to the philosophical, religious, cultural, political, and social underpinningsof western liberal societies vis-à-vis their Muslim communityconstituency. In addition, it has induced several profound identity-relatedquestions pertaining to what it means to be “western” or “a westernMuslim”or, for some, a “Muslim” in theWest. One aspect of this overall dynamic isthe question of the role and the function of faith-based Islamic schoolsoperating in western liberal democracies, as their numbers have mushroomedover the last two decades ...